Adhesive system properties and its behavior under simulated pulpal pressure in sound and caries-affected dentin and aging - Silva, Tânia Mara da; Gonçalves, Lucélia Lemes; Pontes, Solimar Oliveira [UNESP]; Nunes e Reis, Ana Flávia [UNESP]; Mendonça, Rafael Pinto de [UNESP]; Silva, Mateus Rodrigues [UNESP]; Gonçalves, Sérgio Eduardo de Paiva [UNESP] (My University, 2022)
This study aimed to evaluate the bond strength (BS) and adhesive interface characteristics of sound (SD) and caries-affected dentin (CAD) in the presence of simulated pulpal pressure (SPP) and after aging in solvents. The study also evaluated the physical and mechanical properties of the adhesive system under solvent challenge. Seventy-two SD and 36 natural CAD human molars were used. Thirty-six sound molars were submitted to artificial formation of caries by pH cycling (artificial CAD). Chemical analysis was performed in FTIR, and the surface microhardness (KHN) was measured. All specimens had SPP (20 cm H20) and were etched with 37% phosphoric acid, and an adhesive system (Scotchbond Universal, 3 M ESPE) and composite resin block was applied. Tooth-resin sticks were randomly divided into groups according to storage time (24 h and 30 days) and solvents: deionized water (W), 99% ethanol (E) and methyl ethyl ketone (MEK). The specimens were submitted to BS testing (0.5 mm/min; 10 kgf), and the adhesive interface was evaluated by SEM. After aging in solvents, the adhesive samples were evaluated using flexural strength (FS), modulus of elasticity (ME), sorption (SR), and solubility (SL). Chemical differences in dentin were observed through mineral content loss in N-CAD and A-CAD were observed in FTIR analysis. N-CAD showed the lowest mean KHN. Dentin, time, interaction dentin-time, and interaction dentin-time-solvent (p = 0.003 < 0.05) had a statistically significant effect on BS values. The characteristics of the adhesive interface differ among substrates and aging solvents on SEM. Ethanol differed significantly after 30 days with the lowest means values in the analysis of FS, ME, SR, SL. Natural caries-affected dentin, ethanol aging solvent and 30 days of storage time showed to be the most aggressive factors in terms of reducing bond strength, negatively interfering with the quality of the adhesive interface under simulated pulpal pressure. The properties of the adhesive system were more compromised with aging in ethanol.
Keywords: Adhesion; Aging; Caries; Intrapulpal pressure